2017
DOI: 10.1037/tra0000255
|View full text |Cite
|
Sign up to set email alerts
|

Trauma-informed juvenile justice systems: A systematic review of definitions and core components.

Abstract: Objective The US Department of Justice has called for the creation of trauma-informed juvenile justice systems in order to combat the negative impact of trauma on youth offenders and front-line staff. Definitions of trauma-informed care have been proposed for various service systems yet there is not currently a widely accepted definition for juvenile justice. The current systematic review examined published definitions of a trauma-informed juvenile justice system in an effort to identify the most commonly name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
140
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(144 citation statements)
references
References 41 publications
(59 reference statements)
3
140
0
1
Order By: Relevance
“…Branson, Baetz, Horwitz, and Hoagwood () described trauma‐informed care as an “integration of trauma awareness and understanding throughout an organization” (p. 636). Counselors must meet five basic principles of trauma‐informed care: safety, trust, empowerment, choice, and collaboration (Harris & Fallot, ; Knight, ).…”
Section: Trauma‐informed Carementioning
confidence: 99%
“…Branson, Baetz, Horwitz, and Hoagwood () described trauma‐informed care as an “integration of trauma awareness and understanding throughout an organization” (p. 636). Counselors must meet five basic principles of trauma‐informed care: safety, trust, empowerment, choice, and collaboration (Harris & Fallot, ; Knight, ).…”
Section: Trauma‐informed Carementioning
confidence: 99%
“…Listening to the traumatic stories youth share and managing their traumatic stress reactions can impact staff wellbeing and result in a number of symptoms similar to post-traumatic stress such as fatigue, mentally replaying traumatic experiences, or avoiding situations that remind staff of traumatic stories or situations. Promoting work environments that support staff wellbeing by infusing STS prevention practices can reduce staff absenteeism, improve morale, and increase staff cohesion (Branson et al, 2017;Ko et al, 2008). When leadership provides supervision and support that directly helps staff cope with the challenges and stress inherent in juvenile justice settings, those settings are safer and more efficient.…”
Section: Essential Elements For Trauma-informed Juvenile Justice Settmentioning
confidence: 99%
“…But TIC concepts should not be limited to residential group homes and youth welfare institutions [10]. They are relevant for all psychosocial settings, such as juvenile justice institutions [11,12], special needs schools, child and adolescent, as well as, adult psychiatric settings [13], paediatric health care networks [14], shelters for the homeless, refugee centres (9), rehabilitation and detox centres [15] etc. A systematic review [16] of TIC literature on concepts with staff training reported 23 implementation and evaluation studies.…”
Section: Introductionmentioning
confidence: 99%